LITERASI PAJAK MELALUI MEDIA SOSIAL: Tax Literacy Through Social Media - Ni Nyoman Ayu Suryandari; Ni Luh Ade Mutiara Purnamiasih (JAMAS : Jurnal Abdi Masyarakat, 2023)
Around 70% of all state revenue comes from taxes, which are the primary source of income for the government. Most of a nation's progress will be challenging to accomplish without taxes. Almost all national operations are funded by taxes, including the expansion of public infrastructure and spending on staff. The government is forced to make numerous attempts to deepen and extend tax subjects and objects as a result of the growing importance of taxes in the APBN in order to maintain stable state finances. The community's function and support are crucial for this reason. The majority of Indonesian taxpayers work to reduce their tax obligations. A company entity is more profitable the less tax is paid. (1) Conducting Socialization and Education on the Importance of Paying Taxes Through Social Media is the methodology adopted in this study. (2) Promote employee productivity by conducting socialization and education for tracking employee work progress